Polling 'misses' – can Q-methodology help? A case study of the Seanad referendum. Issue 4 (2nd October 2018) - Liston, Vanessa; Harris, Clodagh
ABSTRACT: Accurate information on public opinion is a necessary condition for the effective functioning of democracies. For Lasswell, the open interplay of public opinion with policy is the 'distinguishing mark of popular rule' [Lasswell, H. D. (1941). Democracy through public opinion . Menasha, WI: Banta]. Yet, despite its importance, there is a distinct gap in methods and tools to understand large volumes of public opinion statements on any issue. The 2013 referendum in Ireland on the abolition of the Seanad (Senate) was a prominent example of this gap. Opinion polls were perceived as misleading in suggesting that the referendum was going to pass. Aiming to address opinion noise, and the polarity suggested by opinion polls, we conducted an online study of subjectivity in the week before polling. Using Q-methodology and the stream of public opinion generated during the campaign, we identified three main perspectives on the issue of Seanad abolition. One perspective was in favour of abolition, two opposed the proposal. We conclude that Q-methodology could be used to support opinion polling and political communication by providing a supporting context of the range of social perspectives on the issue at hand.